The CakeML Compiler Explorer Visualizing how a verified compiler transforms expressions - Hjort, Rikard; Holmgren, Jakob; Persson, Christian (My University, 2017)
This report documents the development of a compiler explorer that provides insight to the inner workings of the CakeML compiler. The compiler explorer can interactively present information about an expression’s origin and descent at different stages of compilation. The compiler explorer consists of a web application presenting the expression information and the CakeML compiler with our additions that enable the tracking of expressions. The CakeML compiler is developed in the HOL4 system; the web application user interface in React and the web server in PHP. Getting insight into the inner workings of a compiler is difficult. Several tools exist for other compilers that either explain how a section of the source code relates to the compiled machine code or provide snapshots of different compiler phases. While these features are useful by themselves, combining them would give better insight into the compiler’s transformations. The compiler explorer provides such a combination. The gained insight provided by the compiler explorer can both help developers of the CakeML compiler find new optimizations and improve education about the compiler.
Keywords: Data- och informationsvetenskap; Computer and Information Science